Assessment of functioning of public health facilities in a North Indian state - Singh, Tarundeep; Kankaria, Ankita; Bhatnagar, Nidhi; Jat, Gopal Singh; Kaur, Sukhwinder; Kumar, Rajesh (International Journal Of Community Medicine And Public Health, 2019)
Background: This study was conducted to assess the current status of functioning of health facilities in Punjab. Methods: A checklist based on six building blocks of health system proposed by WHO and the IPHS was developed, validated and pretested. District hospital (DH), one sub district hospital (SDH) and two Community Health Centres or Block Primary Health Centres (CHCs/BPHCs) were randomly selected from each of 22 districts of Punjab and evaluated against checklist. Total score was thus assigned to each facility. Additionally, workload of healthcare workforce, presence of health functionaries as against total posted strength and feedback from administrators of these facilities were also recorded. Results: Health services are concentrated at the DH and SDH. Functional equipment like ECG, oxygen, mask, ambubag etc. are deficient at all levels of health facilities. Nearly 50% of expected medicines were in stock at the DH and SDH and 66% at CHC/BPHC level. Patient to doctor ratio is highest at SDH in outpatient department and CHC/BPHC in emergency section. Number of lab tests per lab technician are highest at CHC/BPHC level. Administrators express the need for reducing staff shortage, more intensive training in the financial and administrative processes and simplification of procedures for management of equipment. Conclusions: Strengthening CHC/BPHC level institutions may improve utilization of public health system and reduce referrals. Lifesaving drugs and equipment need to be available and operational at all levels of facilities. Content of training to administrators needs to be tailored to the felt needs.